Perioperative Risk Factors for Bleeding in Adolescents Undergoing Pedicle Screw Instrumentation for Scoliosis - Soini Venla; Syvänen Johanna; Helenius Ilkka; Helenius Linda; Raitio Arimatias (Switzerland, 2023)
Progressive scoliosis eventually leads to extensive spinal fusion surgery, which carries a risk for significant bleeding. Neuromuscular scoliosis (NMS) patients have an additional inherent risk of major perioperative bleeding. The purpose of our research was to investigate the risk factors for measured (intraoperative, drain output) and hidden blood loss related to pedicle screw instrumentation in adolescents, divided into adolescent idiopathic scoliosis (AIS) and NMS patient groups. A retrospective cohort study with prospectively collected data of consecutive AIS and NMS patients undergoing segmental pedicle screw instrumentation at a tertiary level hospital between 2009 and 2021 was conducted. In total, 199 AIS (mean age 15.8 years, 143 females) and 81 NMS patients (mean age 15.2 years, 37 females) were included in the analysis. In both groups, levels fused, increased operative time, and smaller or larger size of erythrocytes were associated with perioperative blood loss (p < 0.05 for all correlations). In AIS, male sex (p < 0.001) and the number of osteotomies correlated with more drain output. In NMS, levels fused correlated with drain output, p = 0.00180. In AIS, patients' lower preoperative MCV levels (p = 0.0391) and longer operation times, p = 0.0038, resulted into more hidden blood loss, but we did not find any significant risk factors for hidden blood loss in NMS patients.